Analog Kalkon (E)-1,3-bis(4-hydroxyphenyl)prop-2-en-1-one: Sintesis dan Uji Aktivitas Antimicrobia terhadap Bakteri Kontaminan Produk Darah - Wiwit Sepvianti; Serafica Btari Christiyani Kusumaningrum (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Bacterial infection remains a leading cause of death in the world. It caused by incorrect antimicrobial used in the hospital, bacterial resistance caused by prolonged use of antimicrobial, minimum controlling of antimicrobial utilization, and late development of new antimicrobial drugs. Chalcone compounds with particular structure are believed to have the capability as an antimicrobial agent. The objective of this study is to synthesize and examine the activity of chalcone analogue compound with two hydroxyl substituents groups in ring A and B as a characteristics. Chalcone analogue (E)-1,3-bis(4-hydroxyphenyl)prop-2-en-1-one was successfully synthesized by Claisen-Schmidt condensation method and produced a pale-yellow crystalline powder with 89.40% yield as reaction powder. The elucidation of reaction product structure using FTIR and GC-MS. Furthermore, the GC-MS test was obtained one-peak chromatogram with 100% of relative purity and m/z 240 as molecular ions detected according to the target compound of (E)-1,3-bis(4-hydroxyphenyl)-prop-2-en-1-one molecular weight. Antimicrobial activity examination was performed by paper disk diffusion method and the result showed that chalcone analog compound (E)-1,3-bis(4-hydroxyphenyl)prop-2-en-1-one has medium inhibition activity to Staphylococcus aureus as positive gram bacteria, with the clear zone diameter was 9,2 mm in the 25,00 ppm of concentration. This compound were indicated to work selectively into Staphylococcus aureus, because it was not actively inhibit the growth of another bacterial test such as Bacillus sp., Escherichia coli and Acinetobacter